Vegetable seed systems among ethnic minority communities in northern Vietnam - Nabuuma, Deborah; Swaans, Cornelis P.M.; Pham, Thi Mai Huong; Hoang, The Ky; Nguyen, Thi Tan Loc; Ngo, Thi Hanh; Stomph, Tjeerd-Jan (Bioversity International and the International Center for Tropical Agriculture, 2021)
Despite the potential of vegetables for nutrition and income in Northern Vietnam, inadequate access to quality seed is a major constraint affecting production, diversity and diet quality. Both self-saved seed and bought seed are important sources for farmers and are linked to the primary purpose of production, market access, seed production knowledge and skills, and trustworthiness of the source. Vegetable diversity, seasonal availability and seed access varies with ethnic group, location, type of and specific vegetables requiring contextualisation of nutrition-sensitive interventions. There are opportunities for farmer sharing and exchange of seeds, vegetables, and knowledge, for safeguarding diversity, promote dietary quality, and improve farmer income.